2021
DOI: 10.1039/d1cp03049c
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation efficiency and inhibition mechanism of 2′-substituted nucleotide analogs against SARS-CoV-2 RNA-dependent RNA polymerase

Abstract: The ongoing pandemic caused by SARS-CoV-2 emphasizes the need for effective therapeutics. Inhibition of SARS-CoV-2 RNA-dependent RNA polymerase (RdRp) by nucleotide analogs provides a promising antiviral strategy. One common group...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“… 33 , 34 , 47 They can immediately inhibit the next nucleotide addition once it is incorporated into the nascent strand, and previous work has shown the steric effect caused by the 2′-methyl group substitution could facilitate the immediate termination on SARS-CoV-2 RdRp. 48 The above examples have demonstrated that nucleotide analogues with modification on the ribose could serve as promising inhibitors to terminate the nucleotide addition in SARS-CoV-2 RdRp.…”
mentioning
confidence: 99%
“… 33 , 34 , 47 They can immediately inhibit the next nucleotide addition once it is incorporated into the nascent strand, and previous work has shown the steric effect caused by the 2′-methyl group substitution could facilitate the immediate termination on SARS-CoV-2 RdRp. 48 The above examples have demonstrated that nucleotide analogues with modification on the ribose could serve as promising inhibitors to terminate the nucleotide addition in SARS-CoV-2 RdRp.…”
mentioning
confidence: 99%
“…Similarly, mechanistic studies are lacking for SARS-CoV-2 RdRp inhibition by AT-527 ( 16 ), whose base is converted into guanine in vivo to form the active triphosphate metabolite AT-9010 [ 102 ]. However, it should be noted that the uridine analog of AT-9010, sofosbuvir, induces immediate chain termination after incorporation into RNA by SARS-CoV-2 RdRp, likely mediated by strong steric hindrance introduced by its bulky 2′-methyl group [ 103 , 104 ]. The mechanism of action for molnupiravir ( 17 ) is complex and distinct from chain-terminating nucleotides.…”
Section: Rna-dependent Rna Polymerase (Rdrp)mentioning
confidence: 99%
“…Molecular dynamics (MD) simulation has become a useful tool to resolve the dynamics of biological macromolecules at the atomic resolution. Recently, it has been widely utilized for drug screening and examining the mechanisms of nucleotide analogs on the nucleotide addition in SARS-CoV-2 RdRp 4,5,8,[23][24][25][26][27][28] . However, the timescale for one turnover of nucleotide addition cycle has been estimated at several milliseconds for viral RdRps 29,30 , which is difficult to be directly accessed by conventional MD simulations usually covering the timescales up to hundreds of nanoseconds or a few microseconds for the biological macromolecules.…”
Section: Introductionmentioning
confidence: 99%